Development of a physical literacy assessment framework for Chinese preschool children: a Delphi–AHP approach - Tao, Xiaojuan; Zhang, Junkai; Wang, Xiaotian; Tao, Yuliu; Guo, Mingming (Frontiers in Public Health, 2025)
PurposePhysical literacy (PL) during early childhood is crucial for establishing a foundation for lifelong physical activity and holistic development. However, China currently lacks a developmentally appropriate and culturally relevant PL framework for preschool-aged children. This study aimed to develop such a framework using a modified Delphi method and determine the relative importance of its components through the Analytic Hierarchy Process (AHP).MethodThe study employed a multi-phase design comprising a literature review, expert interviews, and two rounds of Delphi surveys with 40 experts across relevant fields. Items were retained if they met the 80% agreement threshold or were justified based on expert consensus and developmental relevance. The AHP was conducted using YAAHP software to calculate the relative weights of indicators at all levels.ResultsThe finalized framework comprises four core dimensions—motivation and confidence, physical competence, knowledge and understanding, and physical activity participation—encompassing 15 first-level and 49 second-level indicators. Dimensional weights were relatively balanced, with motivation and confidence (25.68%) and physical activity participation (25.52%) slightly exceeding physical competence (25.38%) and knowledge and understanding (23.42%).ConclusionThis study presents the first national PL framework specifically designed for Chinese preschoolers. It provides theoretical grounding and practical guidance for future PL assessments and early intervention strategies. The inclusion of risk prevention behaviors and 24-h movement behaviors—physical activity, sedentary behavior, and sleep—marks a significant advancement over existing models.